Scottish Arbitration Handbook A Practitioner's Guide. - Parratt, David R. (Edinburgh University Press, 2021)
In 2010, the Arbitration (Scotland) Act 2010 came into force with the aim of modernising Scots law on arbitration. Building on the previous edition, this book reviews the last 10 years: the development of the law in Scotland, the use of the Act and the Rules of Court, and how it all works in practice.